Parents' perceptions of physical activity for their children with cancer: a qualitative meta-synthesis - Gu, Yan; Yu, Jie; Li, Liangjian; Pan, Liming; Ma, Dongmei; Cui, Lin; Cui, Chunxue; Guo, Fang (Frontiers in Pediatrics, 2025)
BackgroundThe the number of cases of cancer in children is increasing annually. Physical activity (PA) can enhance the future outcomes and quality of life of children with cancer. However, studies have shown that children with cancer have low levels of PA and that the majority don't adhere to the guidelines' recommendations for physical activity.ObjectiveThe aim was to synthesize parents' perceptions of PA for their children with cancer and to explore barriers and facilitators, thereby providing a basis for promoting PA in children with cancer.MethodsThe PubMed, Web of Science, Cochrane Library, EMBASE, CINAHL and three Chinese databases were systematically searched. Qualitative empirical reports from the onset of the corresponding databases until October 2023 were included in the review. Two independent reviewers performed the review, carried out the data extraction process and evaluated the study quality.FindingsSix studies in all were included. Parents’ perceptions of PA for their children with cancer were synthesized into the following three themes of analysis: (1) barriers to participation in PA; (2) facilitators of participation in PA; and (3) seeking support.ConclusionOur study identified complex factors that influence physical activity participation in children with cancer, and these findings provide a focus for future interventions. Future research should further explore appropriate, targeted exercise intervention programs to promote children's participation in physical activity.